Assessment of the Basic Law Lesson Consistent with the Opinions of Social Studies Pre-Service Teachers - Oguz Hacat, Sibel (Sciedu Press, 2018)
The aim of the present study is to identify the approach of social studies pre-service teachers to legal topics in the “Basic Law” lesson within the Social Studies Teaching Bachelor’s Degree Program. A case study based on qualitative research methods was employed. The study group consisted of 57 social studies pre-service teachers. Data was obtained using semi-structured interview forms consisting of open-ended questions. The interview form was administered twice, at the beginning and at the end of the semester. Data obtained was analysed using content analysis. At the beginning of the semester, the motives for teaching of the Basic Law lesson were identified in seven different categories. Consistent with the opinions of the pre-service teachers, it was determined that these categories were related to 26 subcategories. However, the motives for teaching the Basic Law lesson were indicated in 10 different categories at the end of the semester. Consistent with the opinions of the pre-service teachers, it was determined that the latter categories were related to 29 subcategories. In conclusion, it was demonstrated that the content of the lesson influenced students’ opinions. Based on the results of the study and the literature review, there are a limited number of studies that focus on the teaching of legal topics in social studies education in our country. Thus, in the future, further studies should be carried out in this field.
Keywords: 4. Education; 16. Peace & justice